Effects of novel coronavirus Omicron variant infection on pregnancy outcomes: a retrospective cohort study from Guangzhou - Xiao, Huanshun; Chen, Cheng; Huang, Shan; Zhang, Wenni; Cai, Shuangming; Hou, Xiangling; Luo, Yiping; Lin, Yu (Frontiers in Medicine, 2023)
Since 2022, Omicron has been circulating in China as the main variant of the novel coronavirus, but the impact of infection with the Omicron variant on pregnant women and newborns is still unknown. To further understand the clinical features of Omicron infection during pregnancy and the effect of Omicron infection on pregnancy outcomes. This study retrospectively analyzed the data of 93 confirmed cases of novel coronavirus infection and 109 non-infected patients admitted to the isolation ward of Guangdong Provincial Maternal and Child Health Hospital from December 1, 2022, to January 31, 2023, and statistically analyzed the clinical characteristics of Omicron variant infection during pregnancy and its impact on pregnancy outcomes and analyzed the further impact of underlying diseases on Omicron infection in pregnant women.This study showed that the incubation period of COVID-19 infection was 0.99±0.86 days, 94.38% of patients had fever or other respiratory symptoms, and the lymphocyte count in the infected group decreased compared with the uninfected group, and the lymphocyte count in patients with pregnancy complications or complications was further reduced. Compared with the non-infected group, the patients in the infected group had prolonged APTT and PT, decreased platelet count and fibrinogen, and the above indexes were statistically significant. COVID-19 infection during pregnancy increased the rate of cesarean section compared with uninfected pregnant patients, and COVID-19 infection in patients with gestational diabetes mellitus resulted in a 4.19-fold increase in the incidence of cesarean section.There was no significant difference in gestational age between the two groups, the incidence of intrauterine distress was higher in the infection group, the amniotic fluid was cloudy, and there was no difference in neonatal respiratory distress. No positive cases of neonatal COVID-19 infection were observed.Our findings suggest that most patients infected with Omicron during pregnancy have febrile respiratory symptoms with lymphopenia, but the incidence of critical illness is low; Both Omicron infection and gestational diabetes have further increased the incidence of caesarean section, and no evidence of vertical transmission of Omicron has been found in the study.